2018
DOI: 10.1002/pros.23479
|View full text |Cite|
|
Sign up to set email alerts
|

Adipocytes affect castration‐resistant prostate cancer cells to develop the resistance to cytotoxic action of NK cells with alterations of PD‐L1/NKG2D ligand levels in tumor cells

Abstract: Blocking the adipocyte effect by inhibiting the IL-6/leptin-JAK/Stat3 signaling axis may enhance NK cell mediated immunity to CRPC cells and this strategy may help to develop future therapeutics to treat obese PCa patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 60 publications
0
27
0
1
Order By: Relevance
“…Former in vitro and in vivo studies showed that leptin has a diminishing effect on cytotoxicity and cytokine secretion of NK cells and modulates NK cell surface receptor expression [ 14 , 24 , 25 , 35 ]. The discrepancy between the increased leptin receptor expression in obesity and the altered functionality in NK cells after leptin incubation could be explained by an impaired post-receptor leptin signaling cascade in NK cells [ 14 , 24 , 27 , 35 ]. Besides leptin, other obesity-related metabolites, like adiponectin or IL-6, are shown to influence NK cell functionality [ 15 , 21 , 22 , 27 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Former in vitro and in vivo studies showed that leptin has a diminishing effect on cytotoxicity and cytokine secretion of NK cells and modulates NK cell surface receptor expression [ 14 , 24 , 25 , 35 ]. The discrepancy between the increased leptin receptor expression in obesity and the altered functionality in NK cells after leptin incubation could be explained by an impaired post-receptor leptin signaling cascade in NK cells [ 14 , 24 , 27 , 35 ]. Besides leptin, other obesity-related metabolites, like adiponectin or IL-6, are shown to influence NK cell functionality [ 15 , 21 , 22 , 27 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigated NK cell functionality in obesity. In vitro analyses revealed evidence for an altered cytotoxicity, cytokine secretion, and phenotype of primary NK cells and NK cell lines after incubation with the adipocytokines leptin or adiponectin as well as adipocytokine containing supernatants derived from cultured adipocytes [ 21 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results demonstrated a reduced cytotoxicity of ACM-treated human NK cells against prostate cancer cells. This effect has been shown to be primarily mediated via the IL-6 and leptin content in the ACM (126). Furthermore, ACM-treatment of NK cells resulted in a decrease of granzyme-and TRAIL-positive NK cells, but an increase of IFN-γ production, although the effects of ACM seem to be species-specific and depending on the different phases of adipogenesis the ACM was harvested (69,77).…”
Section: Insights About Expression Of Adipokine Receptors On Nk Cellsmentioning
confidence: 99%
“…9 Moreover, recent studies indicate that interleukin-6 (IL-6) and leptin secreted by the adipocyte induce PD-L1 expression in cancer cells via activation of the JAK/Stat3 pathway. 10 A switch from white fat to brown fat caused by tumor cells 11 can also promote the direct expression of PD-L1 in adipocytes. 12 Therefore, targeting TAAs may be used to interrupt and eliminate a significant source of nutrients and immune protection for tumor cells.…”
Section: Introductionmentioning
confidence: 99%